A Novel Complementary Method for the Point-Scan Nondestructive Tests Based on Lamb Waves. (25th November 2014) - Gorgin, Rahim; Wu, Zhanjun; Zheng, Yuebin
Abstract : This study presents a novel area-scan damage identification method based on Lamb waves which can be used as a complementary method for point-scan nondestructive techniques. The proposed technique is able to identify the most probable locations of damages prior to point-scan test which lead to decreasing the time and cost of inspection. The test-piece surface was partitioned with some smaller areas and the damage probability presence of each area was evaluated. A 0 mode of Lamb wave was generated and collected using a mobile handmade transducer set at each area. Subsequently, a damage presence probability index (DPPI) based on the energy of captured responses was defined for each area. The area with the highest DPPI value highlights the most probable locations of damages in test-piece. Point-scan nondestructive methods can then be used once these areas are found to identify the damage in detail. The approach was validated by predicting the most probable locations of representative damages including through-thickness hole and crack in aluminum plates. The obtained experimental results demonstrated the high potential of developed method in defining the most probable locations of damages in structures.